PERANAN BEKUDO BONO DI KECAMATAN TELUKMERANTI DALAM PENGEMBANGAN WISATA BONO DI KABUPATEN PELALAWAN - Eko Adi Putra; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Bekudo Bono is a people's game using a wooden boat. The role of Bekudo Bono in Telukmeranti Village brings many benefits especially in the field of tourism in Telukmeranti, while the purpose of this study is to determine the role of Bekudo Bono, to know the contribution obtained through Bekudo Bono, to know the perception of the people of Telukmeranti Bekudo Bono and tourism development in the District Pelalawan, to know the participation of the community in supporting the special interest tourism event of Bekudo Bono. The method used in this study is a historical research method consisting of four stages, namely heuristics (collecting resources), source criticism, interpretation, and historiography. Data obtained from the interviews plus the data obtained from the book. The data obtained from interviews and literature studies are then analyzed in their own language. The location of the study was conducted in Telukmeranti Sub-District of Telukmeranti Regency of Pelalawan Regency. This research was conducted from the issuance of the research permit until this thesis is completed. Data collection techniques used are interview techniques, literature study and documentation techniques. The results show that Bekudo Bono has a very important role in tourism in Telukmeranti Village.Keywords: Role of Bekudo Bono, Tourism Development Bekudo Bono